Significance of the epidermal barrier and sensitisation to household allergens to the development of atopic march for primary prevention - E. E. Varlamov; A. N. Pampura; A. N. Asmanov (Бюллетень сибирской медицины, 2018)
Atopic march is a variant flowing of atopia that begins in early childhood as atopic dermatitis, then developinto other allergic diseases (bronchial asthma, allergic rhinitis) at an older age. The state of the epidermal barrier and sensitization to inhaled allergens are considered as predictors for the development of atopic march. Data on the importance of these factors in the development of atopic march and information about possible approaches to prevention are presented in this article.